Assessment of village water and sanitation committee in a district of Tamil Nadu, India - S R Ganesh; S Ganesh Kumar; Sonali Sarkar; Sitanshu Sekhar Kar; Gautam Roy; K C Premarajan (Wolters Kluwer Medknow Publications, 2013)
A descriptive study was conducted among 75 members of five Village Water and Sanitation Committees (VWSCs) and 15 local residents in Tamil Nadu, India to assess committee's formation and decision making process. There were 64% females and rest were males, all aged between 20 years and 45 years. A total of 50.7% of them passed 12 th standard and 29.3% belonged to self-help groups. Although, all of them were aware about presence of guidelines, none of them knew its contents. About 20% opined that meetings were not being conducted regularly. All members said that they had problems in attending meeting regularly, take decisions if at least 10 (67%) members are present and fund was not adequate for 1 year period. One-third of local residents did not know the committee formation process and none of them aware about guidelines. Formation and decision making process of VWSC should be improved to tackle the sanitation problem.